FGL1 and FGL2: emerging regulators of liver health and disease - Jiongming Chen; Lei Wu; Yongsheng Li (BMC, 2024)
Abstract Liver disease is a complex group of diseases with high morbidity and mortality rates, emerging as a major global health concern. Recent studies have highlighted the involvement of fibrinogen-like proteins, specifically fibrinogen-like protein 1 (FGL1) and fibrinogen-like protein 2 (FGL2), in the regulation of various liver diseases. FGL1 plays a crucial role in promoting hepatocyte growth, regulating lipid metabolism, and influencing the tumor microenvironment (TME), contributing significantly to liver repair, non-alcoholic fatty liver disease (NAFLD), and liver cancer. On the other hand, FGL2 is a multifunctional protein known for its role in modulating prothrombin activity and inducing immune tolerance, impacting viral hepatitis, liver fibrosis, hepatocellular carcinoma (HCC), and liver transplantation. Understanding the functions and mechanisms of fibrinogen-like proteins is essential for the development of effective therapeutic approaches for liver diseases. Additionally, FGL1 has demonstrated potential as a disease biomarker in radiation and drug-induced liver injury as well as HCC, while FGL2 shows promise as a biomarker in viral hepatitis and liver transplantation. The expression levels of these molecules offer exciting prospects for disease assessment. This review provides an overview of the structure and roles of FGL1 and FGL2 in different liver conditions, emphasizing the intricate molecular regulatory processes and advancements in targeted therapies. Furthermore, it explores the potential benefits and challenges of targeting FGL1 and FGL2 for liver disease treatment and the prospects of fibrinogen-like proteins as biomarkers for liver disease, offering insights for future research in this field.